2016
DOI: 10.15537/smj.2016.9.14075
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of repeat penetrating keratoplasty in eyes with failed penetrating keratoplasty

Abstract: Objectives:To report the outcomes of penetrating keratoplasty (PKP) surgeries in eyes with failed PKP.Methods:This was a retrospective, non-comparative, descriptive case series. Thirty eyes of 30 patients with failed PKP comprised our study group, they were reviewed from January 2007 to December 2012 at the King Khaled Eye Specialist Hospital, Riyadh, Kingdom of Saudi Arabia. Data were collected on best corrected visual acuity before and after one week, one month, 3 months, 6 months, one year, and 2 years foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
1
3
0
1
Order By: Relevance
“…As expected in accordance with our previous and other studies [11,18,2426] , repeated keratoplasties demonstrated a poorer prognosis that initial keratoplasty, with a clear increasing trend of risk in both univariate and multivariate analysis. This is probably due to deteriorated condition of the corneal bed, probability of increased intraocular pressure during previous keratoplasty, and the violation of anterior chamber immunological privilege in patients with more than one PK procedure.…”
Section: Discussionsupporting
confidence: 93%
“…As expected in accordance with our previous and other studies [11,18,2426] , repeated keratoplasties demonstrated a poorer prognosis that initial keratoplasty, with a clear increasing trend of risk in both univariate and multivariate analysis. This is probably due to deteriorated condition of the corneal bed, probability of increased intraocular pressure during previous keratoplasty, and the violation of anterior chamber immunological privilege in patients with more than one PK procedure.…”
Section: Discussionsupporting
confidence: 93%
“…Se encontró que el riesgo de desarrollo de glaucoma fue más alto en córneas perforadas. [26] Otro aspecto sumamente importante que repercute en la supervivencia de un trasplante, es el antecedente de queratoplastia previa, la cual si bien proporciona mejoría de la agudeza visual hasta en un 47% de los ojos al año, [27] también incrementa el riesgo de falla y rechazo. [23,25,[28][29] Por otro lado, están los aspectos no clínicos, como por ejemplo la procedencia del tejido donante o la técnica quirúrgica, muestran que los botones donantes grandes a menudo se consideran un factor de riesgo para la falla del injerto inmunológico; al igual que el retraso en la epitelización o defecto epitelial persistente, contribuyendo a una mayor tasa de complicaciones de la superficie ocular, [30] siendo considerados factores que han mostrado influenciar en los resultados.…”
Section: Estado Del Arteunclassified
“…[ 1 2 6 7 8 9 10 11 ] At the time of surgery, the majority of our patients had the presence of well-known risk factors for graft failure such as failed graft (50%), PAS (66.67%), deep vascularization (27.77%), and glaucoma (38.88%) either singly or in combination. [ 5 12 13 ] All these preoperative factors could have also increased the chances of postoperative complications such as glaucoma and rejection in our patients. In 50% of patients with failed graft, a repeat graft was planned.…”
Section: Discussionmentioning
confidence: 98%
“…However, 30% of patients with failed grafts, all aged >65 years, refused a repeat keratoplasty owing to prolonged follow-up and poor primary outcomes. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%